ERK3 and DGKζ interact to modulate cell motility in lung cancer cells - Myers, Amanda K.; Morel, Marion; Gee, Stephen H.; Hoffmann, Katherine A.; Long, Weiwen (Frontiers in Cell and Developmental Biology, 2023)
Extracellular signal-regulated kinase 3 (ERK3) promotes cell migration and tumor metastasis in multiple cancer types, including lung cancer. The extracellular-regulated kinase 3 protein has a unique structure. In addition to the N-terminal kinase domain, ERK3 includes a central conserved in extracellular-regulated kinase 3 and ERK4 (C34) domain and an extended C-terminus. However, relatively little is known regarding the role(s) of the C34 domain. A yeast two-hybrid assay using extracellular-regulated kinase 3 as bait identified diacylglycerol kinase ζ (DGKζ) as a binding partner. DGKζ was shown to promote migration and invasion in some cancer cell types, but its role in lung cancer cells is yet to be described. The interaction of extracellular-regulated kinase 3 and DGKζ was confirmed by co-immunoprecipitation and in vitro binding assays, consistent with their co-localization at the periphery of lung cancer cells. The C34 domain of ERK3 was sufficient for binding to DGKζ, while extracellular-regulated kinase 3 bound to the N-terminal and C1 domains of DGKζ. Surprisingly, in contrast to extracellular-regulated kinase 3, DGKζ suppresses lung cancer cell migration, suggesting DGKζ might inhibit ERK3-mediated cell motility. Indeed, co-overexpression of exogenous DGKζ and extracellular-regulated kinase 3 completely blocked the ability of ERK3 to promote cell migration, but DGKζ did not affect the migration of cells with stable ERK3 knockdown. Furthermore, DGKζ had little effect on cell migration induced by overexpression of an ERK3 mutant missing the C34 domain, suggesting DGKζ requires this domain to prevent ERK3-mediated increase in cell migration. In summary, this study has identified DGKζ as a new binding partner and negative regulator of extracellular-regulated kinase 3 in controlling lung cancer cell migration.